Digital Signal Processing Applications : Digital Communications - Hassan, M. A.; Hashim, Nik Mohd Zarifie; Mohd Saad, Norhashimah; Ab Hadi, Nik Azran; Salleh, Azahari; Ja'afar, Abd Shukur (International Journal for Advance Research in Engineering and Technology, 2015)
-